Rancang Bangun Grade Monitoring Assist pada D3K Caterpillar Berbasis Mikrokontroler sebagai Akurasi pada Pekerjaan Operator Dozer - Abdul Halim; Mangkona Mangkona; Abdul Muis; Irfan Andika Sakti (Fakultas Teknik, 2021)
In the process of construction work, operators need accuracy in the process of finishing land leveling works such as road highway building, land reclamation, large commercial, landfill installation, so as to increase productivity. Therefore, the purpose of this research is to manufacture and implement a ground leveling finishing tool using Arduino IDE software and Atmega 328 microcontroller on the Dozer D3K Caterpillar heavy equipment unit. The placement of a series of components from the Grade Monitoring Assist includes the ultrasonic sensor on the lift cylinder, gyro and accelerometer at the top center of the blade, as well as a display that displays the results of parameter readings. Connections between components in Grade Monitoring Assist are cables that integrate all installed components. The results of testing the movement of the blade up and down position to get an accuracy value of 97.30% and an error of 2.70%. While the movement of the blade down position has an accuracy value of 96.50% and an error of 2.50%. And Tests by moving the blade according to the implement movement angle at the maximum blade angle position (either side) with an average error value of 1.48o, cutting ditches (angle V) an average error value of 0.676o